THE IMPACT OF PROJECT-BASED LEARNING ON CREATIVE THINKING AND COGNITIVE LEARNING OUTCOMES AMONG HIGH SCHOOL STUDENTS - Ramadan, Asbul Dio; Wicaksana, Ervan Johan; Mataniari, Raissa (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Creative thinking skills in 21st-century learning have become essential competencies that students must possess; however, these skills have not been fully explored within the learning process, resulting in suboptimal learning outcomes. Therefore, an alternative instructional model is needed that can actively engage students in the learning process. One such model is Project-Based Learning (PjBL). This study aims to determine the impact of the PjBL model on students' creative thinking abilities and cognitive learning outcomes. The research was conducted at SMAN 11 Kota Jambi using a quantitative method. The research design employed was quasi-experimental, specifically the Non-randomized Control-Group Pretest-Posttest Design. The subjects were 10th-grade students (Phase E), selected through purposive sampling. Data analysis was conducted using One Way MANCOVA. Results from the analysis indicate that the PjBL model has a significant impact on students' creative thinking and cognitive learning outcomes, showing a moderate effect on creative thinking skills and a strong effect on cognitive learning outcomes.